Pengaruh Marketing Mix terhadap Loyalitas Pelanggan pada Perum Bulog Subdivre Lampung Tengah - Gustama, Nando (Universitas Muhammadiyah Metro, 2021)
Marketing is an important influence for the progress of a company. This is inseparable from the increasing number of competitors between companies. So, companies need to implement a strategic marketing concept. The marketing concept aims to provide satisfaction with consumer wants and needs. This study aims to determine the effect of the marketing mix which includes: product, price, location, promotion on customer loyalty at Bulog Sub-Division of Lampung Tengah. The population in the sample of this study were customers of Bulog Subdivre Lampung Tengah. The sampling technique in this research is accidental sampling. Sampling using explanatory survey method, with a sample of 68 respondents. The analysis used is multiple linear regression. The results of the study as a whole show that the variables of product, price, location and promotion have a significant and significant effect on customer loyalty at Bulog Bulog Subdivre, Lampung Tengah.